Cyclic Di-Adenosine Monophosphate: A Promising Adjuvant Candidate for the Development of Neonatal Vaccines - Darío Lirussi; Sebastian Felix Weissmann; Thomas Ebensen; Ursula Nitsche-Gloy; Heiko B. G. Franz; Carlos A. Guzmán (MDPI AG, 2021)
Underdeveloped immunity during the neonatal age makes this period one of the most dangerous during the human lifespan, with infection-related mortality being one of the highest of all age groups. It is also discussed that vaccination during this time window may result in tolerance rather than in productive immunity, thus raising concerns about the overall vaccine-mediated protective efficacy. Cyclic di-nucleotides (CDN) are bacterial second messengers that are rapidly sensed by the immune system as a danger signal, allowing the utilization of these molecules as potent activators of the immune response. We have previously shown that cyclic di-adenosine monophosphate (CDA) is a potent and versatile adjuvant capable of promoting humoral and cellular immunity. We characterize here the cytokine profiles elicited by CDA in neonatal cord blood in comparison with other promising neonatal adjuvants, such as the imidazoquinoline resiquimod (R848), which is a synthetic dual TLR7 and TLR8 agonist. We observed superior activity of CDA in eliciting T helper 1 (Th1) and T follicular helper (TfH) cytokines in cells from human cord blood when compared to R848. Additional in vivo studies in mice showed that neonatal priming in a three-dose vaccination schedule is beneficial when CDA is used as a vaccine adjuvant. Humoral antibody titers were significantly higher in mice that received a neonatal prime as compared to those that did not. This effect was absent when using other adjuvants that were reported as suitable for neonatal vaccination. The biological significance of this immune response was assessed by a challenge with a genetically modified influenza H1N1 PR8 virus. The obtained results confirmed that CDA performed better than any other adjuvant tested. Altogether, our results suggest that CDA is a potent adjuvant in vitro on human cord blood, and in vivo in newborn mice, and thus a suitable candidate for the development of neonatal vaccines.